DEZVOLTARE SUSTENABILĂ VERSUS MARKETING OFENSATOR - Tabarcea, Ala; Tullio, Romita (CEP USM, 2022)
In spite of the fact that the specialized literature abounds in sustainability content, modest research that would concern the relationship between sustainability and marketing strategy examine this addiction, especially from the perspective of companies. A study conducted with the masters confirmed, once again, that when the transformation that happened and the altitude of their customers is neglected, their spiritual height, but also the ability of many to slowly ', logically, guiding -constantly from the urge, 'consume what you have to consume', the familiar approach of marketing, which integrates various concepts, including those of sustainability and durability, becomes vain. Therefore, we have set ourselves as purpose: 1. Argumentation of the cases of absurd incorporation of durability and sustainability in philosophy and arithmetic marketing; 2. Investigating practices, that from our point of view, are offensive to customers, even in the context in which more and more companies embrace the imperative of sustainable and/or sustainable development.
SUSTAINABLE DEVELOPMENT VERSUS OFFENSIVE MARKETING
Keywords: sustainable development; humanist strategy